Impact of International Labour Migration of Nepal - Mishra, Manamaya (Patan Pragya, 2020)
Nepalese history has maintained long-term labour migration high intensity through 2014 and will continue. It was estimated that at least 7.3 percent of the total population would be engaged in longtermlabour migration in 2017 (compared to 6.3% at the time of survey). Long-term labourmigration is more likely to originate from rural areas (61%) than urban areas. It is clearly men-led with 93 per cent men and only 7 per cent women, and this gender imbalance will continue in the near future. Most long-term migrant workers originate from Central and Western Development Regions (67%) and are more likely to work in GCC countries and Other countries, while those from Mid-Western and Far-Western Development Regions migrate mostly to Asian countries, mainly India (continuing historical migration pattern towards this destination selected data generated from migrant workers’ and households’ surveys carried out within the Research and Policy Dialogue Initiative on Migration and Remittances in Nepal. The article aims to assist the Government of Nepal in developing evidence-based policies to connect effectively the link between migration and development.